A Meta-analysis on the Role of Children in Severe Acute Respiratory Syndrome Coronavirus 2 in Household Transmission Clusters. (6th December 2020) - Zhu, Yanshan; Bloxham, Conor J; Hulme, Katina D; Sinclair, Jane E; Tong, Zhen Wei Marcus; Steele, Lauren E; Noye, Ellesandra C; Lu, Jiahai; Xia, Yao; Chew, Keng Yih; Pickering, Janessa; Gilks, Charles; et al.
Abstract: The role of children in the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains highly controversial. To address this issue, we performed a meta-analysis of the published literature on household SARS-CoV-2 transmission clusters (n = 213 from 12 countries). Only 8 (3.8%) transmission clusters were identified as having a pediatric index case. Asymptomatic index cases were associated with a lower secondary attack in contacts than symptomatic index cases (estimate risk ratio [RR], 0.17; 95% confidence interval [CI], 0.09-0.29). To determine the susceptibility of children to household infections the secondary attack rate in pediatric household contacts was assessed. The secondary attack rate in pediatric household contacts was lower than in adult household contacts (RR, 0.62; 95% CI, 0.42-0.91). These data have important implications for the ongoing management of the COVID-19 pandemic, including potential vaccine prioritization strategies. Abstract : In household transmission clusters of SARS-CoV-2, children are unlikely to be the index case. Children are also less likely than adults to be infected with SARS-CoV-2 from a family member.